Process evaluation of a randomised controlled trial intervention designed to improve rehabilitation services for Aboriginal Australians after brain injury: the Healing Right Way Trial - Judith M. Katzenellenbogen; Jane White; Melanie Robinson; Sandra C. Thompson; Amy Epstein; Mandy Stanley; Jane Klobas; Emma Haynes; Elizabeth A. Armstrong; Juli Coffin; Rachel Skoss (BMC, 2024)
Abstract Background Healing Right Way (HRW) aimed to improve health outcomes for Aboriginal Australians with stroke or traumatic brain injury by facilitating system-level access to culturally secure rehabilitation services. Using a stepped-wedge randomised controlled trial (RCT) design (ACTRN12618000139279, 30/01/2018), a two-pronged intervention was introduced in four rural and four urban hospitals, comprising 1.Cultural security training (CST) for staff and 2.Training/employment of Aboriginal Brain Injury Coordinators (ABIC) to support Aboriginal patients for 6-months post-injury. Three-quarters of recruited patients lived rurally. The main outcome measure was quality-of-life, with secondary outcomes including functional measures, minimum processes of care (MPC); number rehabilitation occasions of service received, and improved hospital experience. Assessments were undertaken at baseline, 12- and 26-weeks post-injury. Only MPCs and hospital experience were found to improve among intervention patients. We report on the process evaluation aiming to support interpretation and translation of results. Methods Using mixed methods, the evaluation design was informed by the Consolidated Framework for Implementation Research. Data sources included minutes, project logs, surveys, semi-structured interviews, and observations. Four evaluation questions provided a basis for systematic determination of the quality of the trial. Findings from separate sources were combined to synthesise the emerging themes that addressed the evaluation questions. Three components were considered separately: the trial process, CST and ABIC. Results The complex HRW trial was implemented to a satisfactory level despite challenging setting factors, particularly rural-urban system dynamics. Patient recruitment constraints could not be overcome. The vulnerability of stepped-wedge designs to time effects influenced recruitment and trial results, due to COVID. Despite relatively high follow-up, including to rural/remote areas, data points were reduced. The lack of culturally appropriate assessment tools influenced the quality/completeness of assessment data. The ABIC role was deemed feasible and well-received. The CST involved complex logistics, but rated highly although online components were often incomplete. Project management was responsive to staff, patients and setting factors. Conclusions Despite mostly equivocal results, the ABIC role was feasible within mainstream hospitals and the CST was highly valued. Learnings will help build robust state-wide models of culturally secure rehabilitation for Aboriginal people after brain injury, including MPC, workforce, training and follow-up.